China's macroeconomic imbalances: causes and consequences - John Knight; Wei Wang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
In recent years China has experienced two forms of extreme macroeconomic imbalance: an expenditure imbalance in the sense of very high investment and very low consumption, giving rise to rapid capital accumulation; and an imbalance between expenditure and pro-duction, producing external imbalance, i.e. a huge surplus on the current account of the balance of payments. Both imbalances imply a low rate of time discount by both govern-ment and society: consumption in the present is forgone in favour of consumption in the future. The paper examines how these imbalances came about, and goes on to consider whether they can be sustained and how they might be redressed. There is no evidence that the rapid capital accumulation has reduced the rate of profit on capital and thus the incen-tive to invest. However, persistent external imbalance poses a threat to investment if it ge-nerates excess liquidity and asset bubbles. The current account surplus rose remarkably in the years 2004-7. This was associated with exogenous increases in competiveness and in saving, both attributable to the economic reform policies. On current policies, the surplus is likely to rise again once the world economy recovers from its recession. This poses three sorts of problems, each of which is examined in turn: difficulties for macroeconomic stabi-lization policies; risk of capital loss on the foreign exchange holdings; and the threat of re-taliation by China's trading partners. A combination of internal and external policies will be required to redress the imbalance.
URN:NBN:fi:bof-201408071937
Keywords: E21; E22; E61; F32; F41; F51; 330; China; investment; consumption; current account; exchange rate; external im-balance; macroeconomic imbalance